2022
DOI: 10.3389/fphar.2022.919553
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Reduces Anxiety Associated With Inflammatory Bowel Disease By Acting on Cannabinoid CB1 Receptors in the Ventral Hippocampus in Mice

Abstract: The therapeutic effects of electroacupuncture (EA) on the comorbidity of visceral pain and anxiety in patients with inflammatory bowel disease (IBD) is well known. It has been known that the ventral hippocampus (vHPC) and the cannabinoid type 1 receptors (CB1R) are involved in regulating anxiety and pain. Therefore, in this study, we determined whether EA reduces visceral pain and IBD-induced anxiety via CB1R in the vHPC. We found that EA alleviated visceral hyperalgesia and anxiety in TNBS-treated IBD mice. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
2
2
0
Order By: Relevance
“…Therefore, another main question this study seeks to answer is the mechanisms behind this phenomenon. Findings of the current study suggest that EA may promote mitochondrial biogenesis in a CB1R-dependent manner, in agreement with extensive evidence from our group and others’ previous studies ( Sun et al, 2016 ; Hu et al, 2022 ). Additionally, accumulating evidence has emphasized CB1R and mitochondrial biogenesis’s crucial roles in the PNS and CNS ( Bai et al, 2017 ; Sun et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, another main question this study seeks to answer is the mechanisms behind this phenomenon. Findings of the current study suggest that EA may promote mitochondrial biogenesis in a CB1R-dependent manner, in agreement with extensive evidence from our group and others’ previous studies ( Sun et al, 2016 ; Hu et al, 2022 ). Additionally, accumulating evidence has emphasized CB1R and mitochondrial biogenesis’s crucial roles in the PNS and CNS ( Bai et al, 2017 ; Sun et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…These results are also supported by studies that observed benefits of applying acupuncture on Crohn's disease [60][61][62] with possible positive effects on visceral pain [63], alleviating symptoms of visceral hypersensitivity and protecting the gastrointestinal tract [64] and assisting in the management of associated anxiety and depression symptoms [65,66].…”
Section: Electro-acupuncture On St25 Cv6 and Cv12 For Crohn's Diseasesupporting
confidence: 67%
“…Previous studies have suggested that EA can have beneficial effects on colitis. 33 , 34 This study aimed to showcase EA’s effects on obese IBD mice, encompassing weight reduction, diminished fat accumulation, and inflammation mitigation. Additionally, EA exhibited inhibitory effects on colonic ferroptosis in IBD-afflicted mice, concurrently activating the Nrf2/HO-2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%